Translating women : different voices and new horizons - von Flotow, Luise, 1951-; Farahzad, Farzaneh (New York : Routledge, 2017)
This book focuses on women and translation in cultures 'across other horizons' well beyond the European or Anglo-American centres. Drawing on transnational feminist connections, its editors have assembled work from four continents and included articles from Morocco, Mexico, Sri Lanka, Turkey, China, Saudi Arabia, Columbia and beyond. Thirteen different chapters explore questions around women's roles in translation: as authors, or translators, or theoreticians. In doing so, they open new territories for studies in the area of 'gender and translation' and stimulate academic work on questions in this field around the world. The articles examine the impact of 'Western' feminism when translated to other cultures; they describe translation projects devised to import and make meaningful feminist texts from other places; they engage with the politics of publishing translations by women authors in other cultures, and the role of women translators play in developing new ideas. The diverse approaches to questions around women and translation developed in this collection speak to the volume of unexplored material that has yet to be addressed in this field.
Includes bibliographical references and index.
Keywords: Translating and interpreting; Feminism and literature; Women translators